2007
DOI: 10.1084/jem.20062395
|View full text |Cite
|
Sign up to set email alerts
|

Requirements for survivin in terminal differentiation of erythroid cells and maintenance of hematopoietic stem and progenitor cells

Abstract: Survivin, which is the smallest member of the inhibitor of apoptosis protein (IAP) family, is a chromosomal passenger protein that mediates the spindle assembly checkpoint and cytokinesis, and also functions as an inhibitor of apoptosis. Frequently overexpressed in human cancers and not expressed in most adult tissues, survivin has been proposed as an attractive target for anticancer therapies and, in some cases, has even been touted as a cancer-specific gene. Survivin is, however, expressed in proliferating a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
66
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 95 publications
(69 citation statements)
references
References 42 publications
3
66
0
Order By: Relevance
“…The stimulation of EpoR by Epo binding increases GATA-1 gene expression is a positive feedback loop (Chiba , 1991) and induces GATA-1 phosphorylation and activation (Zhao et al, 2000). In addition, survivin was shown to be required for red blood cell formation (Leung et al, 2007). These observations have two consequences.…”
Section: Discussionmentioning
confidence: 99%
“…The stimulation of EpoR by Epo binding increases GATA-1 gene expression is a positive feedback loop (Chiba , 1991) and induces GATA-1 phosphorylation and activation (Zhao et al, 2000). In addition, survivin was shown to be required for red blood cell formation (Leung et al, 2007). These observations have two consequences.…”
Section: Discussionmentioning
confidence: 99%
“…As evidence for a functional role of survivin in red blood cell maturation, we observed that a subset of survivin heterozygous mice exhibited a decrease in the percentage of enucleated cells as compared to wildtype littermates. 6 Together, these findings led us to hypothesize that survivin plays a novel role in enucleation of erythroblasts.…”
Section: Introductionmentioning
confidence: 99%
“…Germline deletion of Survivin leads to early embryonic lethality at E3.5 [15]. Tissue-specific knockout of Survivin in thymocytes, neuronal precursors, endothelial cells or haematopoietic progenitors resulted in impaired cell proliferation, cell cycle arrest, mitotic spindle defects or apoptosis, all illustrating a physiological role for survivin in normal cell development [16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%